Heaviest rainfall ever recorded in relation to its return period - AYYAR, P. S. HARIHARA; TRIPATHI, N. (MAUSAM, 1971)
For hydrological design purposes, it is not sufficient to take into account only the heaviest rainfall recorded at the place, Instead, the return period of the heaviest rainfall recorded and also the extreme values of rainfall for different return periods should he taken into account. The return period and the probability of occurrence of the heaviest rainfa.11 recorded at selected observatory stations in India have been computed and presented.